Osteological differences in allopatric populations of the Odontophrynus occidentalis group from Western Argentina - Crespo, E. G. (1983)
An osteological comparison of new-metamorphosed specimens from three populations of the O. occidentalis group was carried out. The results confirm the accentuated differentiation of the Sierra Famatina population.